2019
DOI: 10.3390/ma12244170
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Features of Wound Dressings Based on Butyric-Acetic Chitin Copolyesters—Results of Clinical Trials

Abstract: The article presents the results of clinical trials of wound dressings whose main ingredient is butyric-acetic chitin copolyester (BAC 90:10). It is a chitin derivative soluble in typical organic solvents. During the trial, the dressings were used on wounds resulting from venous insufficiency or diabetes. The trial evaluated the safety of use and efficacy of three forms of the dressing including porous membrane (Medisorb R Membrane), porous membrane with silver (Medisorb R Ag), and powder (Medisorb R Powder). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Dental surgery clinical trials also found chitosan-based wound treatments to significantly shorten bleeding time and improve wound healing for patients undergoing minor surgery and tooth extractions [167,168]. Clinical trials examining the effect of chitosan on a range of other wounds also exhibited very promising results, with improved cell adherence, hemostasis and re-epithelialization [164,171], less itching and sensitivity [171], less exudate and odor [175], and reductions in wound healing time [170,173], post-hemodialysis puncture site bleeding [173], and rebleeding [174] in diabetic, puncture, superficial, skin graft, and sinus postoperative wounds. Chitosan has also been utilized in clinical trials for treatment of ulcers with notable reductions in exudate, pain on dressing removal, wound area and depth when compared to traditional Vaseline gauze dressings [176,177].…”
Section: Human Clinical Trials Utilizing Chitin and Chitosan For Wounmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental surgery clinical trials also found chitosan-based wound treatments to significantly shorten bleeding time and improve wound healing for patients undergoing minor surgery and tooth extractions [167,168]. Clinical trials examining the effect of chitosan on a range of other wounds also exhibited very promising results, with improved cell adherence, hemostasis and re-epithelialization [164,171], less itching and sensitivity [171], less exudate and odor [175], and reductions in wound healing time [170,173], post-hemodialysis puncture site bleeding [173], and rebleeding [174] in diabetic, puncture, superficial, skin graft, and sinus postoperative wounds. Chitosan has also been utilized in clinical trials for treatment of ulcers with notable reductions in exudate, pain on dressing removal, wound area and depth when compared to traditional Vaseline gauze dressings [176,177].…”
Section: Human Clinical Trials Utilizing Chitin and Chitosan For Wounmentioning
confidence: 99%
“…Human clinical trials utilizing commercially available and custom-made chitin and chitosan wound treatments, resulting in significant improvements in the healing of ear, nasal, oral, and skin wounds, in addition to treatment of ulcers and serious hemorrhages. Data from [162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177]. Chitosan, unknown [177] These wound treatments have experienced significant success in oral clinical trials where they have been used to treat aphthous stomatitis (mouth ulcers), postoperative and tooth extraction wounds.…”
Section: Human Clinical Trials Utilizing Chitin and Chitosan For Wounmentioning
confidence: 99%
“…Their use leads to a reduction in the ulcer area and its depth. These dressings were assessed as having a high safety profile [38].…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to their unique structure, dressings drain wound exudates beyond its environment, thus restoring the proper course of the cell reconstruction process. The ability to biodegrade in contact with the wound secretion eliminates the need to replace dressings, so the newly formed granulation tissue is not disturbed -cell reconstruction processes run smoothly [38].…”
Section: Chitin Co-esters In Dressing Materialsmentioning
confidence: 99%
“…The choice of calcium alginate (matrix A) [86][87][88] and chitosan (matrix B) [89] as polysaccharide substrates was based on their proven usefulness in regenerative medicine. Despite its hydrophobic nature, butyryl-acetyl chitin co-polyester (BAC 9:1), a component of the ternary matrix C), has been found to promote tissue regeneration and wound healing [90][91][92]. A key feature of all the polysaccharides used in this study is their proven biodegradability in vivo (breakage of polysaccharide chains results in soluble forms that are easily removed by the body once the substrate has fulfilled its desired functions).…”
Section: Discussionmentioning
confidence: 99%